Descriptive Study on Emotional Intelligence Amidst Nursing Undergraduates of Choosed Nursing Institute - Binal Joshi1 , Franny Joel Emmanuel2 , Vipin Vageriya3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Emotional intelligence is that portion of the human soul which persuades people to perform.Emotional intelligence may accommodate student nurses while managing their personal and patients’emotions, manifesting genuine emotional reaction, while being empathetic and effective communicatorundergraduate nurse determine effective way to visualize emotions without introducing conflict of interest.It also helps in dealing with instinctive feelings, such as anger and dissatisfaction, in a nurse–patientrelationship.Objectives: Researchers have set the objectives of Computing the level of emotional intelligence amongnursing undergraduates, and to find out the Correlation among different components of emotional intelligencetool.Methodology: Researchers have used Descriptive research design, 179 Nursing Undergraduates of onenursing Institute, have been recruited as a sample with Consecutive non probability technique. Researchershave used standardized schutte self reported emotional intelligence tool in the form of 5 point likert scale,Results: Researchers have identify that 130 sample ( 72.63% ) have average emotional intelligence, 25sample ( 13.97%) have good emotional intelligence, 24 sample (13.41%) have poor emotional intelligence.Mean distribution suggests that perception of emotions has mean of 35.13, managing own emotions mean is35.21, managing others emotions mean is 31.41, Utilization of emotions mean is 24.55.Conclusion: It also reciprocates that each of the components of emotional intelligence tool have positivecorrelation with each other components. Thus Researchers have concluded that to boost the emotionalstability an individual should emphasize their own self. This may also lead in positive social change,reducing emotional conflicts, resulting in high productivity